(untitled) (Raparin Journal of Humanities (RJH), 2026)
The annual principle is considered one of the procedural principles of the public budget, which essentially signifies the preparation of the state’s public budget for a fiscal year. This principle is crucial from the perspectives of state politics, the economy, and finance. In terms of politics, the annual principle ensures continuous oversight by the legislative authority over the activities of the executive authority. With regard to the economy, it provides the state with accurate estimates of its expenditures and revenues and highlights the challenges facing the economy in a way that enables officials to take the necessary measures to address them. The central problem of this study is that the federal state of Iraq suffers from non-compliance with the annual principle of the public budget. Therefore, the authors, using a descriptive and analytical method, seek to examine the principle, its historical emergence, the justifications for its application, and the exceptions to adherence, along with analyzing the causes, effects, and negative consequences of non-compliance through three main arguments. In conclusion, the authors argue that complying with the annual principle of the public budget is of paramount significance, and its application is justified by political, economic, and financial factors for which specific legal provisions have been enacted. Yet, the state has often violated the principle, which has consequently left negative impacts on the state’s overall capability. Non-adherence to the principle has weakened state institutions and undermined the economic, financial, security, and legal performance of governments. The authors ultimately present several recommendations, including the amendment of relevant constitutional and legal provisions and addressing the challenges of adherence in order to remove obstacles and eliminate the harmful effects of non-compliance with the principle.